PENGARUH PENERAPAN HANDOUT BERMUATAN KECERDASAN KOMPREHENSIF DALAM MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KOMPETENSI FISIKA SISWA KELAS X MIA SMAN 10 PADANG - Aviatul Hasanah; Djusmaini Djamas; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2016)
One of factor causes low learning outcomes is using of students learning materials that do not support the achievement  all the competence such as spiritual attitude, social attitude, knowledge, and skills.  The purpose of this research were to determine the competency of the Physics students and to investigate the effect handout containing comprehensive intelligence in problem-based learning model to the competency of Physics students grade X at SMAN 10 Padang.  Type of research was quasi experimental research with randomized control group only design.  The population of this research were students grade X MIA SMAN 10 Padang who were registered in the 2015/2016 academic year.  Sampling technique was purposive sampling continued with cluster random sampling.  There were three instruments in this research, those are observation sheet of attitude domain, test sheet of knowledge domain and rating scale of skill domain,  Based on the data analysis could be presented the result of this research.  using  handout containing comprehensive intelligence has given significant effect toward Physics competency of students grade X SMAN 10 Padang with 0,05 signification level